Evaluation of cytotoxicity of different root canal sealers and their effect on cytokine production - Kangarloo, Ali; Sattari, Mandana; Rabiee, Faranak; Dianat, Seyed Omid (Iranian Endodontic Journal, 2009)
INTRODUCTION: Endodontic sealers are in direct contact with periradicular tissues and play a critical role in regeneration and pathogenesis of periradicular diseases. The aim of this study was to compare cytotoxicity of four different types of sealers including AH plus, Sankin, Tubliseal EWT and Apexit as well as their effect on cytokine release of L929 fibroblasts. MATERIALS AND METHODS: In this experimental study, cells were cultured in Complete Medium Culture (CMC) and then divided into two test groups. In group 1, sealers were added to cell culture wells immediately after mixing. In group 2, sealers were added to cell cultures 3 hours after mixing. Cell viability was evaluated by MTT assay after 4, 24 and 168 hours. The amount of Interleukin-6 (IL-6) released in response to the sealers was also evaluated by ELISA technique on fibroblasts after 24 hour period. Data were analyzed using Kruskal-Wallis and Mann Whitey-U tests. RESULTS: Significant differences were seen in cytotoxicity in both groups (P<0.001). The least cytotoxic sealers were AH Plus and Sankin respectively, whereas Tubliseal EWT showed the greatest cytotoxicity. Production of IL-6 was significantly different among studied groups (P<0.001). The highest IL-6 level was observed in Tubliseal EWT and Sankin groups; which was statistically significant (P<0.001). CONCLUSION: AH plus has less cytotoxicity and induces less IL-6 release. Tubliseal EWT has greater cytotoxicity and induces more IL-6 release than other sealers. This should be considered during their routine use in root canal treatments.